Compostos bioativos em uvas ‘Isabel’: influência da radiação UV-C e potencial protetor em modelo de colite ulcerativa em ratos - Maurer, Luana Haselein (2018)
The aims of this study were to evaluate the effect of post-harvest UV-C irradiation on antioxidant markers of 'Isabel' grapes and to study the protective potential of grape peel powder (GPP) and its bioactive fractions (free phenolic compounds, EP; fiber-bound phenolics, NEP-F; and dietary fiber, F) in a rat model of colitis. 'Isabel' grapes were treated with different doses of UV-C (0, 0.5, 1, 2, and 4 kJ/m2) and stored for 1, 3 or 5 days to evaluate their enzymatic and non-enzymatic antioxidant capacity by determining the activity of superoxide dismutase (SOD), catalase (CAT) and glutathione reductase (GR), the content of thiols, and the ability to remove superoxide and peroxyl radicals. One day after irradiation with UV-C, thiol levels and antioxidant enzyme activities increased, especially when the intermediate doses (1 and 2 kJ/m2) were used. The same doses also promoted an increase in the total phenolic content whereas 0.5 and 4 kJ/m2 had no effect. Anthocyanin levels increased by ~35% after irradiation with 1 kJ/m2 of UV-C, which was considered the hormetic dose, however there was no change in the anthocyanin profile. In the experiment involving the induction of colitis, Wistar rats were fed with diets supplemented with 8% of GPP or its bioactive fractions (EP, NEP-F, and F) for 15 days before colitis induction (intrarectal administration of 2,4,6-trinitrobenzenesulfonic acid, TNBS, 10 mg/animal) and for a further 7 days after induction. EP, NEP-F, and F were added at amounts equivalent to those found in the GPP. GPP had 25% of fiber and 776 mg phenolic compounds/100g. EP had 80% anthocyanins, whereas NEP-F had 78% of fiber and 7.7% of fiber-bound phenolics. The weight gain prior to the induction of colitis did not differ among groups. Feed intake was reduced after colitis and only the EP group did not reestablish feed intake, beyond exhibiting adverse effects after TNBS exposure. Such damages were not observed when phenolics were bound to the matrix, as in GPP. Colitis increased lipid peroxidation, protein oxidation, nitric oxide (NO) levels, and inflammatory cytokines at tissue and systemic level, beyond activating the NF-κB pathway. GPP reduced inflammatory markers, restored SOD and CAT activities, and decreased tissue oxidation and NO levels. Only NEP-F reduced protein expression of pNF-κB and neutrophil infiltration. Colitis reduced the thiol levels and the activity of GR, SOD, CAT, glutathione peroxidase (GPx), and glutathione-S-transferase (GST) in the colon, in addition to increasing the mRNA expression of both subunits of glutamate-cysteine ligase (GCL). GPP and NEP-F restored GPx activity. All experimental diets reduced the protein expression of the IKK-β, and NO levels in the colon, in addition to partially increasing thiol levels and restoring GR and GST activities. The effect about GSH system was attributed to the GSH recycling rather than the de novo synthesis. Colitis also induced apoptosis in colonic tissue and NEP-F and F reduced this effect. The bioactive fractions of GPP did not protect against macroscopic damage and EP aggravated the lesion. GPP, EP, and NEP-F reduced the mRNA expression of claudin-2, whereas F fraction increased the mRNA expression of zonula occludens and occludin. Colitis reduced by ~30% the short-chain fatty acids (SCFA) production and GPP and NEP-F reversed this effect, while F fraction was ineffective. The protective effects of GPP in the colon were associated with inhibition of the NF-κB pathway, reduction of NO and inflammatory cytokines, improvement of the antioxidant enzymes activity, intestinal barrier function, and SCFA production. Dietary fiber and fiber-bound phenolics were more effective than soluble phenolics to protect against colitis and the consumption of grape peel powder could be investigated as a benefic alternative for patients with intestinal inflammation.